De Quervains Thyroiditis (sub-acute thyroiditis) - Nabi, G; Rahman, NMW; Azad, MAK; Hassan, M; Bonik, M (Mediscope, 2017)
Inflammatory diseases of the thyroid can be classified into three broad categories: acute, subacute and chronic thyroiditis. Subacute disease includes granulomatous or De Quervains thyroiditis and lymphocytic thyroiditis or silent thyroiditis. The gland swells up and is very painful and tender. As thyroid hormones are discharged into the blood, patient becomes hyperthyroid clinically but the gland cannot take up iodine so the radioactive iodine uptake is very low. The hyperthyroidism generally resolves after a few weeks. The relief of pain by giving NSAID or steroids in this condition is so dramatic as to be almost diagnostic. A 40 year old man, hailing from Nawabganj, Dhaka was diagnosed as De Quervains thyroiditis and treated successfully. In this report, the case condition, procedures of diagnosis and treatment are reported in details. Mediscope Vol. 4, No. 1: Jan 2017, Page 35-37